Relationship between learner motivation and perceptions of an e-learning platform among undergraduates - Raveenthiran, Kiran Ravinasha; Ismail, Lilliati (Medwell Journals, 2018)
This study investigated the relationship between learner motivation and perceptions of an e-Learning platform among undergraduates in a university in Malaysia using the university’ e-Learning platform, PutraBLAST. 125 respondents were selected from undergraduates in the Faculty of Educational Studies. Data were collected using a questionnaire. Descriptive and inferential statistics were used to analyse the data. Findings from the descriptive analysis showed that respondents were moderately motivated when using PutraBLAST. Respondents were also satisfied with the e-Learning environment using PutraBLAST. A moderate positive relationship was found between motivation and perceptions of the e-Learning platform (r = 0.632). This study suggests for the need to incorporate features in PutraBLAST that would enhance motivation as it is positively correlated to perceptions of the e-Learning experiences using the e-Learning platform.